Developing a graphical package for sensor arrays design, optimization and maintenance - N. Jabbar, Ahmed; A. Murdas, Ibrahim (International Journal of Engineering and Technology, 2018)
The sensor arrays are now an essential part of any communication, medical and remote sensing system. These arrays should be designed with utmost performance to ensure the maximum link efficiency. The available commercial sensor arrays design packages are expensive, complicated and cannot be easily modified to accommodate the usersâ€™ needs. This work suggests a solution that is to design an open source specialized application to serve the ever-changing needs of the users. This package is called Sensor Array Design and Optimization (SADO) and it is developed to allow the unexperienced users and the researchers to design, test and optimize their sensor arrays using effi-cient optimization algorithms. The optimization is trying to reduce the sidelobe levels to reduce the interference. The application is simple and friendly to use, with professional graphical results. The predesigned arrays configurations supplied with this package are uniform and random arrays. The built in optimization algorithms are: Artificial Bee Colony (ABC), Biogeography-Based Optimization (BBO) and Teaching Learning Based Optimization (TLBO). The results for various designs and optimization results are also given and compared to indicate the best settings for the user. Some optimization ratios might reach about 50% that represent -3dB reduction in sidelobe level.Â Â